Young Adults, Digital Media, and Religion Broadening the Scope - Sjö, Sofia (Journal for Religion, Film and Media, 2025)
Looking at youth and young adults when researching religion and media is an approach that can lead to important results. Young people are often on the forefront of media developments and are likely to impact how religious groups utilize and incorporate media in their practices. Building on the findings of an international project and earlier research, this article highlights three interconnected areas worthy of more attention in the study of religion and media: the limitation of most studies to specific settings and university students and thus the need to expand this demographic; the importance ofstudying online and offline religion as interconnected and related; the need to study not only religion and media but also how media might contribute to individuals leaving their religious identity behind and provide spaces for atheist identities and communities.